Incidence rate of type 2 diabetes is >50% lower in GrassrootsHealth cohort with median serum 25–hydroxyvitamin D of 41 ng/ml than in NHANES cohort with median of 22 ng/ml. Issue 155 (January 2016) - McDonnell, S.L.; Baggerly, L.L.; French, C.B.; Heaney, R.P.; Gorham, E.D.; Holick, M.F.; Scragg, R.; Garland, C.F.
Highlights: Median 25(OH)D was 41 ng/ml in GRH cohort and 22 ng/ml in NHANES cohort. Type 2 diabetes annual incidence rate was 9.3 per 1000 population in NHANES. Adjusted annual incidence rate of type 2 diabetes was 3.7 per 1000 population in GRH. Higher odds of developing type 2 diabetes for lowest v. highest tertiles in NHANES. Abstract: Higher serum 25–hydroxyvitamin D [25(OH)D] concentrations have been associated with lower risk of type 2 diabetes. This study compared incidence rates of type 2 diabetes among participants aged ≥20 years in two U.S. cohorts with markedly different median 25(OH)D concentrations. The median 25(OH)D concentration in the GrassrootsHealth (GRH) cohort was 41 ng/ml (N = 4933) while in the 2005–6 National Health and Nutrition Examination Survey (NHANES) it was 22 ng/ml (N = 4078) ( P < 0.0001). The adjusted annual incidence rate of type 2 diabetes was 3.7 per 1000 population (95% confidence interval = 1.9, 6.6) in the GRH cohort, compared to 9.3 per 1000 population (95% confidence interval = 6.7, 12.6) in NHANES. In the NHANES cohort, the lowest 25(OH)D tertiles (<17, 17–24 ng/ml) had higher odds of developing diabetes than the highest tertile (OR: 4.9, P = 0.02 and 4.8, P = 0.01 respectively), adjusting for covariates. Differences in demographics and methods may have limited comparability. Raising serum 25(OH)D may be a useful tool for reducing risk of diabetes in the population.